ANALISIS PENENTUAN HARGA POKOK PRODUKSI PADA USAHA PENGETAMAN KAYU AURA KONSEN DENGAN MENERAPKAN METODE ACTIVITY ABASED COASTING - Aura, Aisyah; ZL, Nikken Azzahara; Wedyati, Nur Azzahra; Suriyanti, Linda Hetri; Nurjannah, Hafidjah (Research in Accounting Journal (RAJ), 2022)
Aura Konsen's Wood Setting Business is a trading company that determines the production cost by applying the Activity Based Coasting System Method so that the company does not make mistakes in making decisions regarding the production cost. The research used is descriptive research, using data collection techniques in the form of interviews with the owners of the company. It can be concluded that the calculation of the cost of production using the Activity Based Coasting System Method gives higher results than using the traditional method. The results of the Activity Based Coasting System method are more accurate. According to the calculations that have been done, that two methods have a difference with each product of IDR 118,583 for Doors, IDR 18,545 for Windows, and IDR 326 for Sills. All overhead costs are calculated in detail so that it can be seen how much the actual costs incurred in production activities can be.